Performance of Corn Hybrids with Contrasting Maturity in Northeastern Kansas - L. N. Lingua; I. Massigoge; A. J. P. Carcedo; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2023)
Corn (Zea maysL.) hybrid selection is one of the most important agricultural management decisions made by farmers. Both genetic yield potential and adaptation to the local environment vary widely across corn hybrids, and have a direct impact on yield and input costs. This study compared the performance of corn hybrids with contrasting comparative relative maturity (CRM, referring to their growth cycle), to evaluate their differences in crop phenology, grain yield and its components—grain number and grain weight. The field experiment was conducted during the 2022 growing season in Manhattan, KS (U.S.), testing five commercial corn hybrids with contrasting CRM under rainfed conditions. The overall length (days) of crop growth cycle across all corn hybrids ranged from 92 to 120 days, and the grain yield ranged from 102 to 146 bu/a. The variation in grain yield across hybrids was mainly explained by differences in grain number and grain weight.
Keywords: maize; corn; comparative relative maturity; grain yield